2014
DOI: 10.1002/adfm.201401091
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Damage Mitigation from Oriented Nanostructures within the Radular Teeth of Cryptochiton stelleri

Abstract: Chiton are marine mollusks who use heavily mineralized and ultrahard teeth to feed on epilithic and endolithic algae on intertidal rocks. To fulfill this function, chiton teeth must be tough and wear‐resistant. Impressive mechanical properties are achieved in the chiton tooth through a hierarchically arranged composite structure consisting of a hard shell of organic‐encased and highly oriented nanostructured magnetite rods that surround a soft core of organic‐rich iron phosphate. Microscopic and spectroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
135
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(144 citation statements)
references
References 49 publications
3
135
0
6
Order By: Relevance
“…Nanoparticulated surface coatings have been observed in other biological composite materials such as the ultra-hard teeth of the chiton, Cryptochiton stelleri, a marine mollusk. [42] These teeth feature an outermost 2 μm thick layer of densely packed sub-100 nm magnetite particles with no preferred orientation, which cover an underlying rod-like microstructure and provide abrasion resistance. [42] The incorporation of ceramic nanoparticles into epoxy polymers used as matrix materials for fiberreinforced composites has also been shown to improve the toughness as well as Young's modulus of the polymer.…”
Section: A Sinusoidally-architected Helicoidal Biocompositementioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticulated surface coatings have been observed in other biological composite materials such as the ultra-hard teeth of the chiton, Cryptochiton stelleri, a marine mollusk. [42] These teeth feature an outermost 2 μm thick layer of densely packed sub-100 nm magnetite particles with no preferred orientation, which cover an underlying rod-like microstructure and provide abrasion resistance. [42] The incorporation of ceramic nanoparticles into epoxy polymers used as matrix materials for fiberreinforced composites has also been shown to improve the toughness as well as Young's modulus of the polymer.…”
Section: A Sinusoidally-architected Helicoidal Biocompositementioning
confidence: 99%
“…[42] These teeth feature an outermost 2 μm thick layer of densely packed sub-100 nm magnetite particles with no preferred orientation, which cover an underlying rod-like microstructure and provide abrasion resistance. [42] The incorporation of ceramic nanoparticles into epoxy polymers used as matrix materials for fiberreinforced composites has also been shown to improve the toughness as well as Young's modulus of the polymer. [43][44][45] The extent of plastic deformation of the epoxy is enhanced so as to dissipate more energy in regions surrounding the crack tip.…”
Section: A Sinusoidally-architected Helicoidal Biocompositementioning
confidence: 99%
“…Finite element models of the tooth have shown that the leading edge is dominantly loaded in tension while the trailing edge is in compression during scraping events. Moreover, the principal directions of applied stress coincide with the natural rod alignment within the tooth [22], [30]. This difference in loading conditions accounts for the size difference in the rods, as larger diameter rods are favorable for compressive loading [31].…”
Section: Introductionmentioning
confidence: 87%
“…A recent study of the fully mineralized radular teeth of Cryptochiton stelleri has revealed insights into the abrasion resistance of the rod-like microstructure [30]. The hard magnetite shell of the tooth is reminiscent of a fiber-reinforced composite, composed of aligned hexagonal closepacked rods, surrounded by thin regions of organic α-chitin, which run parallel to the longitudinal axis of the tooth ( Figure 1C, D).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation